Liver cirrhosis-epidemiological and Clinical Aspects - Gunnarsdóttir, Steingerður Anna (2008)
Liver cirrhosis is the end-stage of many different chronic liver diseases. Limited data exists on the epidemiology, natural history and complications of liver cirrhosis such as esophageal varices and malignancies in the Nordic countries after the discovery of hepatitis C (HCV). Most hepatocellular carcinomas (HCC) develop in patients with liver cirrhosis but data on the occurrence of other malignancies than HCCs in these patients are scarce. Gastrointestinal (GI) symptoms such as nausea, vomiting, abdominal pain, and diarrhea are common in patients with advanced liver disease but the importance of portal hypertension for these symptoms is unexplored. The aims of the present study were to evaluate the incidence, outcome and complications of liver cirrhosis in a Swedish population and in Iceland and the effects of portal hypertension on small bowel motility and small intestinal bacterial overgrowth (SIBO) in patients with liver cirrhosis. The annual incidence of liver cirrhosis in Gothenburg was 15.3 ±2.4/100.000 compared to 3.3 ±1.2/100.000 in Iceland, p<0.0001. In Gothenburg 50% of the patients had alcoholic cirrhosis compared to 29% in Iceland (p<0.0001). Only 9% of patients died in their first variceal bleeding, that is within one week of their first bleeding episode. Of the patients diagnosed with esophageal varices after a bleeding episode, 55% had a bleeding episode during follow-up compared to only 13% of the patients diagnosed without a bleeding episode. Variables predicting mortality in a multivariate analysis were: Child-Pugh class, bleeding before diagnosis, age and bilirubin levels. Causes of death were in 26% of cases liver failure, 19% variceal bleeding and the rest other causes. Patients with liver cirrhosis had 267 times increased risk of hepatocellular cancer. Among patients with HCV cirrhosis, 19% developed HCC and 20% of those with HCV and alcoholic liver disease (ALD). We observed 13 times increased risk of cholangiocarcinoma and also increased risk for esophageal, pancreatic, pulmonary ...